Implications of the COVID-19 pandemic for state government tax revenues - Stan Veuger; Jeffrey Clemens (American Enterprise Institute (AEI), 2020)
We assess the Covid-19 pandemic's implications for state government sales and income tax revenues. We estimate that the economic declines implied by recent forecasts from the Congressional Budget Office will lead to a shortfall of roughly 106 billion in states' sales and income tax revenues for the 2021 fiscal year.
Keywords: A; 330; State and Local Government Finance; Fiscal Federalism; Tax Bases; Balanced Budget Requirements